Collaborative Assistance Model in the Preparation of the APBDES: Integration of Legal Aspects and Community Participation - Eka Merdekawati Djafar; Fajlurrahman Jurdi; Naswar; Sardil Mutaallif; A. Nur Ilmi Amaliyah Passalowongi; Juwita (STMIK Indonesia Banda Aceh, 2026)
The Draft Village Revenue and Expenditure Budget (RAPBDes) has an important role for villages in managing finances, preparing development plans, and determining the direction of village development policies. However, the problem of formulating the RAPBDes is still a challenge for some villages due to the lack of capacity and education of village officials as budget planners. The Technical Assistance for the Preparation of the RAPBDes service program aims to improve the understanding and skills of village officials in preparing a more effective budget by focusing on the agricultural sector as a support for the village economy. The method in implementing this program involves 30 participants of village officials as targets, by undergoing service from July and August. The results of the program obtained through the post test showed a percentage of 95%, this can be seen through the ability of the village apparatus to answer questions and formulate RAPBDes in accordance with legal legitimacy. This program has succeeded in improving the quality of the RAPBDes policy and has the potential to be applied more widely as a model of assisting the preparation of RAPBDes in other villages.